1999
DOI: 10.1037/0882-7974.14.4.552
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence moderates the relationship between life stress and natural killer cell activity in healthy older adults.

Abstract: A sense of coherence (SOC) has been found to be a strong predictor of health outcomes and life satisfaction in older adults. This study investigated mood and immune effects of anticipated voluntary housing relocation in 30 healthy older adults and 28 age-matched controls and examined whether SOC would buffer effects of relocation on natural killer (NK) cell activity. Movers completed assessments and had blood drawn 1 month before relocation to congregate living facilities; controls were assessed concurrently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 74 publications
0
59
1
Order By: Relevance
“…Yet a study on elderly persons who anticipated relocation to congregate living facilities found that sense of coherence was a moderator for immune functioning in those anticipating a move. Sense of coherence was positively associated with immune functioning in the moving but not in the non-moving group (Lutgendorf, Vitaliano, Tripp-Reimer, Harvey, & Lubaroff, 1999); an indication that sense of coherence might only have a protective effect in situations with high stress.…”
Section: Descriptive Researchmentioning
confidence: 92%
“…Yet a study on elderly persons who anticipated relocation to congregate living facilities found that sense of coherence was a moderator for immune functioning in those anticipating a move. Sense of coherence was positively associated with immune functioning in the moving but not in the non-moving group (Lutgendorf, Vitaliano, Tripp-Reimer, Harvey, & Lubaroff, 1999); an indication that sense of coherence might only have a protective effect in situations with high stress.…”
Section: Descriptive Researchmentioning
confidence: 92%
“…In other studies, SOC is understood as a coping strategy or a dependent variable (Grøholt, Stigum, Nordhagen, & Kö hler, 2003;Oelofsen & Richardson, 2006). Some researchers, however, regard SOC as a mediator (Lutgendorf, Vitaliano, Tripp-Reimer, Harvey, & Lubaroff, 1999). SOC is in this study regarded as a global orientation to life, as a parent coping resource with a direct effect on stress.…”
Section: Social Support and Socmentioning
confidence: 97%
“…The construct can be thought of as a broad measure of resiliency, with higher levels of SOC linked to positive health-related outcomes in various studies among diverse samples (e.g. Fiorentino, 1986;Lutgendorf, Vitaliano, Tripp-Reimer, Harvey, & Lubaroff, 1999).…”
Section: Introductionmentioning
confidence: 99%